Modeling Demonstrates That Folic Acid Fortification of Whole-Wheat Flour Could Reduce the Prevalence of Folate Inadequacy in Canadian Whole-Wheat Consumers. Issue 11 (30th September 2015) - Chan, Yen-Ming; MacFarlane, Amanda J; O'Connor, Deborah L
Abstract: Background: Mandatory folic acid fortification of white-wheat flour and selected other grain products has reduced the prevalence of neural tube defects in Canada; however, the fortification of whole-wheat flour is not permitted. Objective: The objective of this study was to model the impact of adding folic acid to whole-wheat flour on the folate intake distribution of Canadians. Methods: Twenty-four-hour dietary recall and supplement intake data ( n = 35, 107) collected in the 2004 Canadian Community Health Survey 2.2 were used to calculate the prevalence of folate inadequacy (POFI) and the proportion of folic acid intakes above the Tolerable Upper Intake Level (UL). In model 1, folic acid was added to whole-wheat flour–containing foods in amounts comparable to those that are mandatory for white-wheat flour–containing foods. In model 2, a 50% overage of folic acid fortification was considered. Models 3 and 4 included assessment of folate intake distributions in adult whole-wheat consumers with or without a fortification overage. SIDE (Software for Intake Distribution Estimation; Department of Statistics and Center for Agricultural and Rural Development, Iowa State University) was used to estimate usual folate intakes. Results: Mean folate intakes increased by ∼5% in all sex and age groups when whole-wheat foods were fortified (models 1 and 2; P < 0.0001). Folic acid fortification of whole-wheat flour–containing foods did not change the POFI or percentage of intakes above the UL in the general population, whether in supplement users or nonusers. Among whole-wheat consumers, the POFI was reduced by 10 percentage points after fortification of whole-wheat flour–containing foods (95% CIs did not overlap). The percentage of whole-wheat consumers with intakes above the UL did not change. Conclusion: Although folic acid fortification of whole-wheat flour–containing foods is unlikely to change the POFI or proportion of folic acid intakes above the UL in the general Canadian population, this fortification strategy may reduce the POFI in adult whole-wheat consumers.